Sams teach yourself Visual BASIC 2008 in 24 hours : complete starter kit - Foxall, James D. (Indianapolis, Indiana : Sams Publishing, 2008)
Providing readers with 24 structured lessons with step-by-step guidance to real-world programming tasks for developing Windows applications, this work includes practice exercises, tips, notes, and cautions presenting easy-to-understand advice on how to start programming quickly.
The Visual Basic 2008 environment -- Building a user interface -- Making things happen : programming -- Working with data -- Deploying solutions and beyond.
Includes index.
Keywords: VISUAL BASIC (COMPUTER PROGRAM LANGUAGE)